Safety management and its influence on job satisfaction through safety training practices - Al-Ali, Saeed Ali (2013)
Today, Safety management has been acknowledged as an important part of management system in every organization. Employees are the most valuable resource of any organization, and safety management considered as one of the key activities which drive an organization to create a safe working environment. The main purpose of this study is to identify the effect of safety training practices (moderator) to the relationship of safety management on job satisfaction in Saudi Arabia. A total of 213 respondents were selected based on stratified random sampling method from a petroleum organization. A questionnaire was used to collect the data, and it was analyzed using Statistical Package for Social Science (SPSS), it comprised of descriptive statistics, simple linear regression and hierarchal regression. The finding of the study indicates that there is a significant influence of safety management on employees’ job satisfaction. The result also demonstrates that safety training practices does not moderate the relationship of safety training on job satisfaction. The results obtained from the research is very useful to the petroleum’s organization, especially in Saudi Arabia as there are several recommendations for the organizations and future researches to be carried out